Early to medium-term outcomes of uncemented ceramic-bearing total hip arthroplasty in teenagers for paediatric hip conditions. (1st November 2020) - Buddhdev, Pranai K.; Vanhegan, Ivor S.; Khan, Tahir; Hashemi-Nejad, Aresh
Abstract : Aims: Despite advances in the treatment of paediatric hip disease, adolescent and young adult patients can develop early onset end-stage osteoarthritis. The aims of this study were to address the indications and medium-term outcomes for total hip arthroplasty (THA) with ceramic bearings for teenage patients. Methods: Surgery was performed by a single surgeon working in the paediatric orthopaedic unit of a tertiary referral hospital. Databases were interrogated from 2003 to 2017 for all teenage patients undergoing THA with a minimum 2.3 year follow-up. Data capture included patient demographics, the underlying hip pathology, number of previous surgeries, and THA prostheses used. Institutional ethical approval was granted to contact patients for prospective clinical outcomes and obtain up-to-date radiographs. In total, 60 primary hips were implanted in 51 patients (35 female, 16 male) with nine bilateral cases. The mean age was 16.7 years (12 to 19) and mean follow-up was 9.3 years (2.3 to 16.8). Results: The most common indication for teenage hip arthroplasty was avascular necrosis secondary to slipped upper femoral epiphysis (31%; n = 16). Overall, 64% of patients (n = 33) had undergone multiple previous operations. The survival at follow-up was 97%; two patients required revision for aseptic loosening (one femoral stem, one acetabular component). Both patients had fused hips noted at the time of arthroplasty. A further two patients had radiolucent lines but were asymptomatic. At latest follow-up the mean Oxford Hip Score was 44 (31 to 48) and a Visual Analogue Scale measurement of 1.5, indicating satisfactory function. Conclusion: Operating on this cohort can be complicated by multiple previous surgeries and distorted anatomy, which in some cases require custom-made prostheses. We have demonstrated a good outcome with low revision rate in this complex group of patients. Cite this article: Bone Joint J 2020;102-B(11):1491–1496.